PENGARUH CORPORATE GOVERNANCE, LIKUIDITAS DAN KINERJA KEUANGAN TERHADAP NILAI PASAR PERUSAHAAN (Studi Empiris Emiten Yang Mendapat GCG award IICD Tahun 2010-2012) - Faisal Riza (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
This research aims to determine the influence of corporate governance, liquidity and financial performance of the company's market value. The population in this research are listed companies Indonesian stock exchanges that getting GCG award from IICD about 2010 to 2012. Total sample of 50 listed companies with the observations made during the three years, which is from 2010 to 2012 the data sample of 133. The data used are secondary data, which derived of the book Indonesian Capital Market Directory (ICMD) until 2012 for financial ratio analysis and active listed companies listed in IDX that is determined through purposive sampling. Data analysis was performed with the classical assumption and hypothesis testing with multiple linear regression method. The results of this research indicated that the corporate governance index (CGI), current ratio (CR), debt to equity ratio (DER) and return on investment (ROI) have no significant impact on the market value (Tobin's Q) listed companies and otherwise return on equity (ROE ) significantly affects the market value (Tobin's Q).